Memperkenalkan Model Pendidikan Karakter Di SMP Berbasis Layanan Bimbingan Klasikal Kolaboratif Dengan Pendekatan Experiential Learning - Barus, Gendon; Sunyi, Dirtya (SOLUTION, 2023)
The aim of this research is to produce the model of character education in the Junior High School based on classical-collaborative guidance services with experiential learning approach. This model is expected to optimize the role of school counsellors in actualizing the function and the role as implementers of character education in school. This research is designed by adopting the R, D D Model which is developed by Borg Gall, (1983). The first year of this research (2019), preliminary research stages has been build a conceptual framework for the hypothetical model design which is developed of supporting instruments. The second year (2020), the stage has conducted to develop episode focusing on all concretion device models in the form of instruments, drafting modules and tested it through a series of scientific procedures test, validation, revision, simulation to find suitable model. The third year (2021) product of this research has been implemented on thirteen Junior High Schools in various cities in Indonesia. The implementation of this model has shown encouraging results. Analysis results of the model implementation obtained the increasing results of character education between pre-test and post-test, and both teachers and students assessed this model to be more effective than the integrated character education model.